Weight loss in combat sports: prevalence, magnitude, methods, physiological and performance responses - Escobar-Molina, R. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Combat sports athletes are normally classified according to their body mass at competitions in what has been denominated as weight categories. These weight categories differ between combat sports, however, the upper limit of BM for each weight category is commonly separated by 10-15% intervals. The weigh-in process also varies among combat sports, with `official weigh-ins` occurring anywhere from 16h to 3h before the competition. Despite the differences between weight categories, weigh-in processes and physiological demands of combat sports, the prevalence of weight loss prior to competition is higher than 60% in most Olympic combat sports; with weight loss of approximately half of the percentage interval between weight categories (i.e., 5% to 8%) being common. The main methods used by combat sports athletes to decrease body mass include dieting, dehydration, and exercise using heavy clothes or in hot environments. Increased dehydration and the depletion of energy stores are common consequences of such procedures and have a negative impact on aerobic and anaerobic performance when no nutritional intervention is allowed post-weigh-in. For athletes familiarized with these weight loss processes and who use specific refeeding procedures, aerobic and anaerobic performances decrements may be reduced or eliminated. However, the development of eating disorders and other health-related problems are commonly reported in these athletic groups, especially in female combat sports athletes.